Istota odstąpienia od wymierzenia kary za wykroczenia skarbowe - Sawicki, Janusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The essence of a waiver of penalty for tax offences is a theoretical study on the issue of a waiver of penalty or penal measure against a tax offender. The article reviews the most important issues related to that procedure. The aim of the article is to show the essence of a waiver of penalty under the applicable waiver procedure provided for in the Criminal Tax Code. The author examines the rationale behind a waiver of penalty or penal measure for tax offences set out in the Criminal Tax Code and variants of such a waiver total and non-total. In addition, he presents a summary of his findings concerning the practical application of the procedures in Wrocław district courts.
Keywords: istota odstąpienia od kary; przestępstwo skarbowe; zrzeczenie się kary; uzasadnienie i warianty odstąpienia; odstąpienie w praktyce